2017
DOI: 10.3390/socsci6040131
|View full text |Cite
|
Sign up to set email alerts
|

Transnationalism among Second-Generation Muslim Americans: Being and Belonging in Their Transnational Social Field

Abstract: An increase in transnationalism, the ability of individuals and families to travel and maintain relationships across national borders, has led to questions about its impact on identity especially for the children of migrants. When combined with concerns about global and national security such as those that are associated with Muslims and Islam, then questions about the strength national identity are particularly pertinent. This analysis uses the theories of transnational social fields and intersectionality to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…El Guindi's (1999Guindi's ( , 2005 study on the Islamic movement in Egypt suggests that veiling is an Islamic way to assert Islamic nationalism and engage in participatory politics to resist local and colonial oppression. Among American Muslims, women engage in veiling to reassert their ethnic, religious identity as opposed to non-Muslims Byng (2004Byng ( , 2017Read and Bartkowski 2000). Sadiqi and Ennaji (2006), in Morocco, and Aliya hamid Rao's (2015) study on Muslim converts in American mosques, contend that veiling offers power to veiled women and facilitates access to public space, which is a male-dominated space.…”
Section: The Conceptual and Analytical Frameworkmentioning
confidence: 99%
“…El Guindi's (1999Guindi's ( , 2005 study on the Islamic movement in Egypt suggests that veiling is an Islamic way to assert Islamic nationalism and engage in participatory politics to resist local and colonial oppression. Among American Muslims, women engage in veiling to reassert their ethnic, religious identity as opposed to non-Muslims Byng (2004Byng ( , 2017Read and Bartkowski 2000). Sadiqi and Ennaji (2006), in Morocco, and Aliya hamid Rao's (2015) study on Muslim converts in American mosques, contend that veiling offers power to veiled women and facilitates access to public space, which is a male-dominated space.…”
Section: The Conceptual and Analytical Frameworkmentioning
confidence: 99%
“…However, another group of scientists (Basch et al, 2000;Levitt & Glick Schiller, 2004;Purkayastha, 2005;Wolf, 1997) concluded in his research that, thanks to the knowledge of parents' native language, as well as travel to the country of origin, transnational practice, in most cases, is inherited from parents to children. In examining the transnational activities of the second generation of Muslims born in the United States, Byng (2017) concluded that the transnational orientation of the respondents is influenced by their national, religious and gender identity. The results of this study have shown that most respondents identify themselves as Americans and Muslims at the same time.…”
Section: Theoretical Framework Of the Researchmentioning
confidence: 99%
“…The composition of the articles of this special issue show the variety of how Muslim mobility and gender can be studied as dynamic social fields, on the one hand (Byng 2017;Giuliani et al 2017; in this issue). On the other hand, it provides insight into the possibilities of using it as theoretical lens to investigate the respective other fields: Mobility can be used as a theoretical lens (and, therewith, as an inclusive category, see (Kramer 2017) in this issue) to investigate gender (Daoud 2017;Golkowska 2017; in this issue).…”
Section: Contributions In This Issuementioning
confidence: 99%
“…The last section of this issue, entitled Moving and Settling: Identity Negotiations in Muslim Migration Contexts, deals with forms of mobility, in this case, with the special form of migration which serves as the field of investigation here. Michelle Byng works on transnational migration from various Muslim majorities countries to the West and how this form of movement is informed by intersectionality in Transnationalism among Second-Generation Muslim Americans: Being and Belonging in Their Transnational Social Field (Byng 2017). Using qualitative interview data, the author investigates what experiences second generation Muslim Americans face when visiting their parents' country of origin and how this influences their perceptions of their US American identity.…”
Section: Contributions In This Issuementioning
confidence: 99%